Kesejahteraan Psikologi Masyarakat Miskin Penerima Bantuan Modal Usaha dari Yayasan G25 INDONESIA: Studi Kasus di Kabupaten Bangkalan dalam Perspektif Model Kesejahteraan Psikologis Ryff - Oktavian Ismail Johansyah; Suryanto Suryanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Poverty not only leads to economic limitations but also affects individuals’ psychological well-being. Business capital assistance programs as a form of economic empowerment are expected to improve the overall quality of life of low-income communities. This study aims to describe the psychological well-being of low-income communities receiving business capital assistance from the G25 Indonesia Foundation based on Ryff’s Psychological Well-Being Model. This research employed a qualitative approach with a case study design involving two recipients of business capital assistance. Data were collected through observation and in-depth interviews and were analyzed using thematic analysis. The results indicate that business capital assistance contributes to improvements in the psychological well-being of the subjects across all six dimensions of Ryff’s model, namely autonomy, personal growth, environmental mastery, purpose in life, positive relations with others and self-acceptance. The subjects demonstrated increased economic independence, greater awareness of personal potential, enhanced social engagement, clearer life direction and more positive self-acceptance. This study concludes that business capital assistance not only impacts economic aspects but also strengthens the psychological well-being of low-income communities in a holistic manner.